Refractive surgery and dry eye disease. Issue 12 (December 2020) - Recchioni, Alberto
Abstract : Dr Alberto Recchioni discusses the potential for modern refractive surgery procedures to cause dry eye and shares data to support an argument for introducing less invasive procedures to minimise the problem (C76913, one distance learning CET point suitable for optometrists and dispensing opticians).